The Analysis of Reading Comprehension Questions in English Textbook by Using Higher Order Thinking Skill at Grade X of SMAN 2 Padang - Nurul Hapizah Damanik; Yetti Zainil (Journal of English Language Teaching, 2019)
Abstract                           This research was a descriptive research that aimed to identify the reading comprehension questions in English textbook by using Higher Order Thinking Skill. This study also aimed to analyze and evaluate reading comprehension questions in English textbook. The data used in this research is reading comprehension questions of English textbook. The English textbook were from grade X of SMAN 2 Padang. This study used instrument in the form of indicators from HOTS criteria and Bloom’s criteria. From the result of the reading comprehension question in English textbook by using Higher Order Thinking Skill at grade X of SMAN 2 Padang, it showed that the reading comprehension questions had used the HOTS criteria. As a result of the analysis in reading comprehension questions, 36 questions ( 9.7%) Higher Order Thinking Skill questions were found in the reading comprehension questions. The result of this research also found that mostly-used HOTS criteria in the reading comprehension questions is analyzing category. The knowledge dimensions found in the questions are factual knowledge, conceptual knowledge, procedural knowledge, and metacognitive knowledge. Key words: Reading comprehension questions in English textbook, Higher Order                     Thinking Skill, Bloom’s Taxonomy